PENGARUH KEPEMIMPINAN, PENEMPATAN DAN HUBUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. BANK TABUNGAN NEGARA DI PEKANBARU - Thamrin, Kartina; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2017)
The research held in 8 operating office of PT. Bank Tabungan Negara(BTN) in Pekanbaru. The aim is to know the influence of leadership, job placement andwork relationship to employeeâs performance. Population are employees of 8 BTN operatingoffices in Pekanbaru that cosists of 255 employees,while sample number are 156that using Slovin technique and sampling technique by uses cluster sampling and purposivesampling. Data analysis tool is descriptive quantitative by using multiple regressionanalysis. The study reveals that leadership, job placement and work relationship significantlyinfluence employeeâs performance partially and simultaneusly. Job placement wasfound to be the most dominant factor that influences employeeâs performance.